Seasonal Variatins of Polychlorinted Biphenyls compounds in Water of Tigris River , Maysan Province / Iraq - Bahar Kazem, Halima ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
This study dealt with determining the concentrations of polychlorinated biphenyls (PCBs) for the summer2023 and winter 2024 in three stations of the Tigris River in Maysan Province, southern Iraq, where water samples were taken for each station and analyzed using gas color analysis - mass spectrometry (GC-MASS) for the levels of PCBs, and the results showed the discovery of 12 types of PCBs containing (3-9) chlorine atoms in water samples are (PCB18, 28,31,44,52,101, 138, 141,149,153,189,194) and concentrations during winter were higher than during summer, where concentrations ranged between (1.55-3.53) ng/L in water during summer and winter respectively, as environmental factors were determined for each station, as the temperature of air and water in the study sites ranged between (19-40 C) and (12 and 33 C) and the value of PH ranged between (6.57 - 8.67) The salinity ranged between (3.6 - 4.7) mg / L , while the electrical conductivity ranged between (1761-2424 μS/CM), while the concentrations of total dissolved solids TDS ranged between (801-1288) mg / L and has exceeded the permissible limits globally and locally, and in general it was Low-chlorine congeners prevailed during the summer While high chlorine congeners prevailed during the winter, trip, tetrachlorine and heptachlorine congeners dominated PCB18, PCB52, and PCB189 compared to other congeners.